Indigenous Peoples and the Constitution: Implementation of Traditional Rights Recognition in Modern Legal Foundations - dwi, seffiani (PT. Anagata Sembagi Education, 2024)
This article critically examines the historical and legal trajectory of indigenous peoples' rights recognition within the Indonesian Constitution. Drawing on insights from the theory of customary law rights recognition, as elucidated by constitutional scholars reflecting on the struggles of indigenous communities in Latin American contexts, it reveals a notable gap: despite containing elements of rhetorical support, none of Indonesia's Constitutions fully acknowledge or safeguard indigenous peoples' rights. This deficiency has allowed the state considerable latitude to disregard ancestral rights under the pretext of national interest. To address this, a reinterpretation of constitutional provisions pertaining to indigenous rights is advocated, grounded in the ethos of Indonesian unity amidst diversity. Without such a reinvigorated approach, the risk of further erosion or outright negation of indigenous rights looms large.